Silencing microRNA-155 ameliorates experimental autoimmune encephalomyelitis - Murugaiyan, Gopal; Beynon, Vanessa; Mittal, Akanksha; Joller, Nicole; Weiner, Howard L (The Journal of immunology (1950), 2011)
IFN-γ-producing Th1 and IL-17-producing Th17 cells are the key participants in various autoimmune diseases, including multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis (EAE). Although both of these T cell subsets are known to be regulated by specific transcription factors and cytokines, the role of microRNAs that control these two inflammatory T cell subsets and whether targeting microRNAs can have therapeutic effects are not known. In this study, we show that microRNA-155 (Mir-155) expression is elevated in CD4(+) T cells during EAE, and Mir-155(-/-) mice had a delayed course and reduced severity of disease and less inflammation in the CNS. The attenuation of EAE in Mir-155(-/-) mice was associated with a decrease in Th1 and Th17 responses in the CNS and peripheral lymphoid organs. The T cell-intrinsic function of Mir-155(-/-) was demonstrated by the resistance of Mir-155(-/-) CD4(+) T cell-repleted Rag-1(-/-) mice to EAE. Finally, we found that anti-Mir-155 treatment reduced clinical severity of EAE when given before and after the appearance of clinical symptoms. These findings demonstrate that Mir-155 confers susceptibility to EAE by affecting inflammatory T cell responses and identify Mir-155 as a new target for therapeutic intervention in multiple sclerosis.